PERLINDUNGAN HUKUM TERHADAP PROFESI KEPOLISIAN DALAM MENJALANKAN TUGAS POKOK DAN FUNGSI PENYELESAIAN TINDAK PIDANA DI KEPOLISIAN DAERAH (POLDA) PROPINSI KEPULAUAN BANGKA BELITUNG - Shinta Jayanti Apriana (PROGRESIF: Jurnal Hukum, 2016)
Legal protection is very effort to shelther the human dignity and recognize of human rights in the legal field. A country has the responsibility to socialize new regulations to its society so that they will be aware of the law and also of their rights protected by the state. If society’s legal awareness is growing well, then legal protection in this country will run properly. The development of law enforcement is the beginning of the Police Force. It offers a very interesting history in the development of humanity. Despite the progress that goes slowly, the efforrt is gradually continued in line with the development of human civilization. Thus the ask of the Police is to perforn law enforcement, and the authority of its duty is restricted under the law. In reality, the Police offers in Indonesia are not Legal subjects who never made mistake; hence the author deems that the legal rights and obligations of these officers should be similar as the community at large.